Review of renewable energy industry in Beijing: Development status, obstacles and proposals. (March 2015) - Li, Hongze; Guo, Sen; Cui, Liuyang; Yan, Jiaojiao; Liu, Jiaojiao; Wang, Bao
Abstract: Beijing is the capital of China, serving as the center of China's politics, culture and education. The exploitation and utilization of renewable energy has become an important developmental carrier for Beijing, which is also a key channel for optimizing energy consumption structure, building a high-efficiency and low-carbon energy system, relieving the environmental pressure and ensuring the energy secure of Beijing. In this paper, Beijing's renewable energy industry was analyzed. First, Beijing's renewable energy resources, which include biomass energy, solar energy, geothermal energy, wind energy and hydro energy, were introduced from two aspects of energy resource distribution and energy resource utilization. Second, the development status of Beijing's renewable energy industry (including biomass, solar and wind energy industry) was expounded. Then, the obstacles of Beijing's renewable energy industry were analyzed. Finally, some proposals for the healthy development of Beijing's renewable energy industry were put forward, which will contribute to build a clean, safe, efficient and low-carbon energy system for Beijing.